Properties of solutions of optimization problems for set functions - Slawomir Dorosiewicz (International Journal of Mathematics and Mathematical Sciences)
A definition of a special class of optimization problems with set functions is given. The existence of optimal solutions and first-order optimality conditions are proved. This case of optimal problems can be transformed to standard mixed problems of mathematical programming in Euclidean space. It makes possible the applications of various algorithms for these optimization problems for finding conditional extrema of set functions.